EFFECT OF EFFECTIVE SOLID WASTE MANAGEMENT ON SUSTAINABLE DEVELOPMENT IN ANAMBRA STATE - OJAN ECHO,; OKEKE , Dr. M. N; ONUORAH , Dr. N. N.; J. C. OBOREH, (IJRDO - Journal of Business Management, 2019)
This work examined the effect of effective solid waste management on sustainable development in Anambra State. The study aimed to determine the effect ofPoor Funding, Poor recovery and recycling programme, poor legislation and implementation of policy and poor infrastructures and professionals on sustainable development in Anambra State. Relevant conceptual, theoretical and empirical literatures were reviewed. The study was anchored on Cradle to cradle theory. Descriptive survey design was employed in three major cities in Anambra State, which include Anambra central using Awka, Anambra south (Nnewi) and Anambra north (Onitsha). Primary data were employed. The population was 1,350. Sample size was determined through the application of Taro Yamani’s statistical formula to have 309 as the sample for the study. The involved descriptive analysis and correlation analysis. Multiple regression analysis. The study found that poor funding has a significant influence on sustainable development.Poor recovery and recycling programme has a significant effect on sustainable development.Poor legislation and implementation of policy has a significant influence on sustainable development and infrastructures and professionals has a significant influence on sustainable development in Anambra State. Thestudy concludes that effective solid waste managementhas a significant effect on sustainable development in Anambra State. The recommends that government that needs to address some issues of opening of more and not too distant refuse dumps/ landfills, improved fees for the services rendered by the waste service providers.They should be a management approach which should incorporate re-use and recycling, composting and energy generation and waste prevention.Also there should be a review of the legislative aspects of solid waste management in other to work towards achieving the objectives of waste hierarchy. Government and environmental protection agencies and waste management personals should employee experts or exposed their staff to workshops and trainings that meet international standards on technology use, information management and knowledge management